Constituents of essential oils from leaves and seeds of Foeniculum vulgare Mill. cultivated in Bangladesh - Chowdhury, Jasim Uddin; Mobarok, Md Hosnay; Bhuiyan, Md Nazrul Islam; Nandi, Nemai Chandra (Bangladesh Journal of Botany, 2010)
Analysis of essential oils obtained from the seeds and leaves of Foeniculum vulgare Mill. cultivated in Bangladesh revealed that anethole was the major constituent (58.5% in seed oil and 51.1% in leaf oil), followed by limonene (19.6% in seed oil and 22.9% in leaf oil). Other components present in leaf oil included anisaldehyde, fenchyl acetate and fenchone, while seed oil contained fenchone, α-pinene, fenchyl acetate, γ-terpinene and anisaldehyde. Besides, minor constituents like camphene, camphor, myrcene, pahllandrene, ocimene, β-bisabolene and apiol were obtained from seeds and leaves. Key words: Foeniculum vulgare Mill; Essential oil; Anethole; Limonene; Bangladesh DOI: 10.3329/bjb.v38i2.5144 Bangladesh J. Bot. 38(2): 181-183, 2009 (December)